2018
DOI: 10.1080/14786419.2018.1495636
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of 4′,6,7-trihydroxy-5-methoxyflavone from Fridericia chica (Bonpl.) L.G.Lohmann

Abstract: Fridericia chica, Bignoniaceae, is a tropical tree-creeper used as a traditional remedy for a number of diseases, highlighting inflammation. Our objective was to corroborate the popular anti-inflammatory use of the hydroethanolic extract from the leaves (HEFc) and of its isolated 4',6,7-trihydroxy-5-methoxyflavone (5-Omethylscutellarein) [1], described here for the first time. Quantitative analysis indicated 8.77 ± 0.23 mg/g of this compound in the extract. Neither HEFc nor [1] was cytotoxic in vitro. In LPS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…A. chica extract also demonstrated this effect by inhibiting nuclear transcription factor kappaβ, which consequently prevents the formation of inflammatory mediators such as iNOS, COX-2, 5-LOX, and phospholipase A 2 [18]. Studies by Lima et al [32] also observed that in lipopolysaccharide-induced peritonitis in mice, oral pretreatment with hydroethanolic extract of the leaves or with the isolated compound 4′,6,7-trihydroxy-5-methoxyflavone (5- o -methyl scutellarein) led to decreased leukocyte migration to the peritoneal cavity, as well as a reduction in proinflammatory cytokine concentrations (TNFα and IL-1β).…”
Section: Discussionmentioning
confidence: 99%
“…A. chica extract also demonstrated this effect by inhibiting nuclear transcription factor kappaβ, which consequently prevents the formation of inflammatory mediators such as iNOS, COX-2, 5-LOX, and phospholipase A 2 [18]. Studies by Lima et al [32] also observed that in lipopolysaccharide-induced peritonitis in mice, oral pretreatment with hydroethanolic extract of the leaves or with the isolated compound 4′,6,7-trihydroxy-5-methoxyflavone (5- o -methyl scutellarein) led to decreased leukocyte migration to the peritoneal cavity, as well as a reduction in proinflammatory cytokine concentrations (TNFα and IL-1β).…”
Section: Discussionmentioning
confidence: 99%
“…Fridericia chica (synonym Arrabidaea chica) leaves are usually employed as a red dye, in fact, it has traditionally been used by Sinu artisans of the Colombian Caribbean to make the vueltiao hat [2]. The red color obtained from F. chica comes from anthocyanidins, a class of phenolic compounds with known antioxidant properties [3], and extracts from the plant have shown pharmacological activities linked to beneficial health effects, including anti-inflammatory [4], antiproliferative [5], wound healing [6], antispasmodic [7], photoprotective [8], and leishmanicidal [9] activities. Many of these properties are attributed to different flavonoid compounds reported in F. chica, such as isoscutellarein, 6-hydroxyluteolin, hispidulin, scutellarein, luteolin, apigenin, and hispidulin [10], this last a potential compound for neuroinflammation inhibition [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, apigenin (Perrott et al, 2017) and allicin (Borlinghaus et al, 2014) have been shown to exhibit some antitumor activity. Similarly, flavonoids, compounds that are present mainly in vegetables and citrus fruits, also exert anti-inflammatory, antiangiogenetic, and proapoptotic effects (Kohno et al, 2001; Lima et al, 2018; Ferreira de Oliveira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%